Accessibility and inclusivity of playgrounds for children with disabilities in Malaysia - Ab Wahab, Lilawati (Malaysian Institute of Planners, 2022)
Playing is one of the most crucial physical activities for children's development worldwide. Due to the unsuitability of the playground's design and the available play equipment, children with disabilities (CwDs) frequently experience difficulties when playing, especially at public playgrounds, amusement parks, and other recreational areas. They have consistently been mistreated and ignored in several ways. When designing and developing a playground, the accessibility and inclusivity of the space are crucial factors that should be considered. in preparing playgrounds for Children with Disabilities (CwDs). Two objectives are highlighted in this study, 1) to determine the criteria of accessible and inclusive playgrounds for disabled children in Malaysia and 2) to investigate the current accessibility and inclusivity of playgrounds for children with disabilities in Malaysia. The research methodology used is the qualitative method by using semi-structured interviews with caregivers of disabled children. The findings from the study conclude that most of the public playgrounds designed in Malaysia (even including inclusive playgrounds for Children with Disabilities (CwDs)) have still not met the needs of children with disabilities. The findings from this study hopefully will ensure that disabled children in Malaysia have the accessibility to play in inclusive playgrounds happily in the future. © 2022 Malaysian Institute Of Planners. All rights reserved.